Armazenamento de sementes de milho híbrido tratadas com tiametoxam - Rosa, Karla Crystina (2011)
The seed treatment has been widely used in agronomy, since this practice is considered an instrument of control of pests and diseases, as well as an alternative to higher productivity. Thus, it becomes very relevant, because it is linked to the quality, vigor and germination. These attributes can allow the high development of a productive crop. This study aims to evaluate the effect of treatment in corn seeds with thiamethoxam, stored after treatment of 180 days under different conditions. It was conducted at the Seed Processing Unit of Biomatrix Company, at Patos de Minas (MG), Brazil. Seeds from three maize hybrids, received the treatment routinely used by the company (Deltamethrin - Decis®, pirimiphos-methyl - Actellic 500 EC® and Captan). The experimental treatment consisted of using a product based on thiamethoxam (120 mL per 60.000 seeds), combined with storage with and without temperature control. It was evaluated by germination and cold test with soil immediately after treatment and at the 60th, 120th and 180th days of storage. During storage, vigor of corn seeds treated with thiamethoxam is influenced negatively. The physiological quality of corn seeds treated with thiamethoxam hybrid is dependent on the employee.